Análise dos conceitos de autonomia e responsabilidade e o contexto da agência artificial - Leal, Franciele da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
In this work, we propose to develop a critical analysis of the concepts of agency and responsibility in the contemporary technological context in which artificial systems said to be autonomous are produced. Aiming on this goal, we present, firstly, some theories of action, and we problematize the notions of causal event and causal action, object and agent, aiming on clarifying the notion of agency. Following, we analyze the notion of responsible action proposed by Hans Jonas, once he proposes a notion of responsibility considering the contemporary technological development. In particular, we present and discuss the heuristic notion of fear proposed by Jonas (2004) whose goal is to create possible scenarios which may anticipate long-term implications of the use of new technologies and may help to inform society about the possible consequences of their use for the new generations. Finally, we deal more specifically with the legitimacy of the attribution of agency and responsibility to artificial systems, specially robots, from the perspective of Philosophy and Robotics, from theses defended by Hans Jonas (2004, 2013) and Willem Haselager (2005). In their texts, both authors discuss the possibility of attributing agency and responsibility to artificial systems capable of learning and making decisions which surpass the limits of their initial programming. We conclude that it seems problematic both to attribute agency to autonomous artificial systems in the same sense in which human beings are considered to be agents, and to reduce such systems to mere causally determined objects.

Neste trabalho nos propomos a desenvolver uma análise crítica dos conceitos de agência e responsabilidade no contexto tecnológico contemporâneo em que são produzidos sistemas artificiais ditos autônomos. Tendo esse objetivo em foco, apresentamos primeiramente teorias da ação e problematizamos as noções de evento causal e ação causal, objeto e agente, visando clarificar a noção de agência. Analisamos, em seguida, a noção de ação responsável proposta por Hans Jonas uma vez que ele propõe uma noção de responsabilidade considerando o desenvolvimento tecnológico contemporâneo. Em especial, apresentamos e discutimos a noção de heurística do temor proposta por Jonas (2004) cujo objetivo é criar cenários possíveis que antecipem implicações a longo prazo do uso de novas tecnologias e auxiliem a informar a sociedade sobre as possíveis consequências de seu uso para as novas gerações.Por fim, tratamos mais especificamente da legitimidade da atribuição de agência e responsabilidade a sistemas artificiais, especialmente a robôs, na perspectiva da Filosofia e da Robótica, a partir de teses defendidas por Hans Jonas (2004, 2013) e Willem Haselager (2005). Em seus textos, ambos autores discutem a possibilidade de atribuir agência e responsabilidade a sistemas artificiais capazes de aprender e tomar decisões que ultrapassem os limites de sua programação inicial. Concluímos que parece problemático tanto atribuir agência a sistemas artificiais autônomos no mesmo sentido em que se considera que seres humanos são agentes quanto reduzir tais sistemas a meros objetos causalmente determinados.
An analysis of the concepts of autonomy and responsibility and context of the artificial agency
Keywords: Agência; Autonomia; Responsabilidade; Sistemas artificiais autônomos; Heurística do Temor